Analisis Motivasi Kerja, Kepemimpinan Transformasional dan Budaya Organisasi terhadap Kinerja Karyawan Dimediasi Kepuasan Kerja pada Angkatan Kerja Generasi Z - Gilang Pratama Hafidz; Mega Noviyati (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to analyze work motivation, transformational leadership and organizational culture on employee performance mediated by job satisfaction in the generation Z workforce. This research is a quantitative research using non-probability sampling method with 325 respondents. Based on the results of data analysis, it can be concluded that work motivation on job satisfaction does not have a positive effect, organizational culture has the largest positive influence on the performance of Generation Z employees, transformational leadership style and work motivation have a positive influence on the performance of Generation Z employees and then job satisfaction is proven to mediate the three exogenous variables on employee performance.